The Anticholinergic Drug Effect on Decreasing Cognitive in Geriatric Patients at Kota Surakarta General Hospital - Nurlena Ikawati; Fita Rahmawati (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
This leads the geriatric patients to receive multiple drugs regimen (polypharmacy) which include using anticholinergic drugs. Risk of anticholinergics drug use is associated with cognitive impairments that have been demonstrated in experimental and cohort studies. The objective of this study is to determine the profile of anticholinergic drug use and its impact on cognitive reduction in elderly patients at Outpatient Unit Department of Kota Surakarta General Hospital. This study used cohort design. Data were collected through patient medication records and direct interviews to measure the cognitive status of patients using a six-item cognitive impairment test questionnaire (6-CIT). This study divided the respondents into two group; 178 patients (50,6%) took anticholinergic agents, and 174 patients (49,4%) did not use the anticholinergic drugs. Data analysis used Chi-square comparative test and linear regression test with SPSS (Statistical Package for Social Science). The results showed 136 patients or 58,12% use level one anticholinergic drug. The most widely used anticholinergic are diazepam (13,9%) and furosemide (12,5%). The anticholinergic drugs were extensively used by patients who suffer circulatory system diseases as much as 171 (32,1%), followed by endocrine disease, nutrition and metabolic diseases were 83 (15,6%). The number between women and men who take anticholinergics is not significantly different, 91 (51.41%) for women. Whereas by age, the number of most anticholinergic prescribed for patients who are 60 to 74 years is 124 patients (69,66%). There was a significant correlation between anticholinergic drug use in decreasing cognitive function of the geriatric at Outpatient Unit Department of Kota Surakarta General Hospital (p <0,005) proven by r value 0.631.